Pulmonary Function Recovery After Treatment in Drug Sensitive TB: What Factors Matter? - Novery Simbolon; Pandiaman Pandia; Andika Pradana; Taufik Anhar (CV. Inara, 2025)
Background: Indonesia ranks second globally in tuberculosis burden, and up to 50% of treated patients develop pulmonary dysfunction. Objectives: To identify clinical and radiographic factors influencing spirometric recovery after treatment in drug-sensitive pulmonary tuberculosis. Methods: Analytical observational study with cross-sectional design. Population comprised adults (>18 years) in Medan who completed standard drug-sensitive TB therapy within six months. Sixty participants were selected by consecutive sampling. Instruments included spirometry (Global Lung Function Initiative 2022 equations) and chest radiograph scoring. A structured questionnaire captured demographics, TB history, comorbidities, and smoking. Data analysis involved bivariate tests (chi-square, Kruskal–Wallis, Fisher’s exact) and multivariate logistic regression (enter method). Results: Advanced radiographic lesion extent was the only independent predictor of abnormal spirometry (Exp(B)=4.889; 95% CI 1.386–17.241; p=0.014). Other variables lost significance after adjustment. Conclusion: Initial lesion burden on chest radiograph strongly determines pulmonary function recovery post-treatment. Early stratification by lesion extent is recommended for targeted follow-up and rehabilitation